Enhanced contrast synchrotron X-ray microtomography for describing skeleton-associated soft tissue defects in zebrafish mutants - Leyhr, Jake; Sanchez, Sophie; Dollman, Kathleen N.; Tafforeau, Paul; Haitina, Tatjana (Frontiers in Endocrinology, 2023)
Detailed histological analyses are desirable for zebrafish mutants that are models for human skeletal diseases, but traditional histological techniques are limited to two-dimensional thin-sections with orientations highly dependent on careful sample preparation. On the other hand, techniques that provide three-dimensional (3D) datasets including µCT scanning are typically limited to visualizing the bony skeleton and lack histological resolution. We combined diffusible iodine-based contrast enhancement (DICE) and propagation phase-contrast Synchrotron radiation micro-computed tomography (PPC-SRµCT) to image late larval and juvenile zebrafish, obtaining high-quality 3D virtual histology datasets of the mineralized skeleton and surrounding soft tissues. To demonstrate this technique, we used virtual histological thin sections and 3D segmentation to qualitatively and quantitatively compare wild-type zebrafish and nkx3.2-/- mutants to characterize novel soft-tissue phenotypes in the muscles and tendons of the jaw and ligaments of the Weberian apparatus, as well as the sinus perilymphaticus associated with the inner ear. We could observe disrupted fiber organization and tendons in the adductor mandibulae and protractor hyoideus muscles associated with the jaws, and show that despite this, the overall muscle volumes appeared unaffected. Ligaments associated with the malformed Weberian ossicles were mostly absent in nkx3.2-/- mutants, and the sinus perilymphaticus was severely constricted or absent as a result of the fused exoccipital and basioccipital elements. These soft-tissue phenotypes have implications for the physiology of nkx3.2-/- zebrafish, and demonstrate the promise of DICE-PPC-SRµCT for histopathological investigations of bone-associated soft tissues in small-fish skeletal disease models and developmental studies more broadly.